STATUS GIZI PADA ANAK YANG MENDERITA DIARE AKUT DI RSD IDAMAN BANJARBARU - ‘Azizah, Intan Nur; Ringoringo, Harapan Parlindungan; Panghiyangani, Roselina; Hidayah, Nurul; Rahmiati, Rahmiati (Homeostasis, 2023)
Nutritional status is associated with the occurrence of acute diarrhea in children. Nutritional status is a description of the state of the body that is affected by food and nutrient intake. Acute diarrhea is defecation with a frequency of more than three times a day with the consistency of loose or liquid stools lasting less than 14 days. Examination of the nutritional status of toddlers can be obtained from anthropometric measurements. This study aims to describe the nutritional status of children with acute diarrhea at RSD Idaman Banjarbaru. This research is descriptive, a research conducted to provide an overview of the nutritional status of toddlers aged 0-60 months from October 2020 to September 2022. The sample of this study was 60 patients suffering from acute diarrhea with severe dehydration. The data used is secondary data from medical records. The results of this study showed that the nutritional status of weight for age was found for toddlers at very underweight 6.7% and toddlers underweight 28.3%, length/height for age found for short toddlers 8.3% and very short toddlers 3.3%, weight for length/height found toddlers with undernourishment 16.7% and toddlers with malnutrition 15.0%, and BMI/U found toddlers with malnutrition 21.7% and toddlers with malnutrition 16 .7%.